Promoting Interfaith Dialogue and Mitigating Religious Conflicts in Indonesia - Azwar Amar Ma'ruf (As- Sakinah Law Firm & Society of Visual Informatics, 2024)
This article explores Indonesia's diverse cultural and religious landscape, highlighting the challenges and opportunities it presents. It recognizes the historical, political, economic, and geographical factors that have shaped interfaith relations and emphasizes the importance of fostering a culture of interfaith dialogue, mutual understanding, and respect. The article examines strategies such as educational initiatives, community-based programs, media engagement, interfaith dialogues, collaboration between religious leaders, and supportive government policies. It emphasizes the pivotal role of education, community initiatives, and technology in shaping perceptions and promoting inclusivity. Additionally, it highlights the importance of legal frameworks and governmental support in safeguarding religious liberty and mitigating religious disputes. The article advocates for building bridges across religious divides, fostering unity, and creating a harmonious society that celebrates the rich tapestry of Indonesia's religious diversity through a multifaceted approach.